Developing Nature-Based Tourism as a Strategic Sector for Green Growth in Lao PDR : Synthesis Report - World Bank (World Bank, Vientiane, 2019)
Lao PDR faces a great opportunity to develop its tourism sector, in particular nature-based tourism (NBT), to create greener, more resilient economic growth and good jobs from its attractive landscapes and wildlife. Throughout the world, NBT is the fastest growing segment of tourism, and the demand is growing as the urban middle class expands, particularly in Asia. There is an opportunity for less established destinations with rich natural and cultural heritage to contribute to sustainable social and economic development, especially in rural areas and particularly for the benefit of women and young people, who can often be marginalized in socially and economically disadvantaged areas. However, there have been several examples globally, and in Lao PDR, where communities with modest attractions and difficult accessibility were promised large numbers of tourists and resulting incomes, with nothing materializing. This report seeks to assess the potential for NBT, identify barriers to sustainable NBT development, and formulate potential solutions and actions that contribute to the country's green growth ambitions.